Pemberian Edukasi Mengenai Pola Makan Sehat Pada Siswa-Siswi SMP Negeri 5 Sambas - Syahrulizar Arditiya; Abdul Karim; Crisna Aprilia; Dian Hardiyanti; Erdiana Laura; Hesty Sulistiya; Khofifah; Muniza (Hippocampus: Jurnal Pengabdian Kepada Masyarakat, 2022)
In this day and age, ready-to-eat food is more attractive to teenagers because it is easy and short to serve. Fast food is considered contemporary food and is popular among teenagers. Teenagers need to get used to a healthy diet to build a body. Therefore, counseling was carried out with the aim of providing learning about healthy eating patterns to seventh and eighth grade students. This activity was carried out at SMP Negeri 5 Sambas on June 9, 2022 in the form of counseling with the theme "Providing Education Regarding Healthy Eating Patterns for Students of SMP Negeri 5 Sambas". The results of the counseling show that there are still many students who do not understand the importance of a healthy diet, such as implementing breakfast behavior that can help metabolism and concentration processes. After this counseling was carried out, it could be concluded that this activity produced output, namely adding insight and increasing students' knowledge about healthy eating patterns.